A dinâmica da difusão da tecnologia da informação: um estudo comparativo em cooperativas - Silva, Áurea Lúcia (2003)
The technology of information (TI) emerged, since the 70's, with paradigmatic potential, that is, as a technology capable of creating new types of organizations and new patterns in problem solving, besides the power of making possible the increase of productivity in the áreas where technology is utilized. In late 90's, this forecast has not come true, especially in áreas with poor technology, as the agricultural sector. This work, performed in two cooperatives of coffee farmers, from Southern Minas Gerais - Cooperativa Regional dos Cafeicultores em Guaxupé Ltda. (Cooxupé) and Cooperativa de Cafeicultores de São Sebastião do Paraíso (Cooparaíso) - tried to understand the dynamic of the TI diffusion and to perceive the factors capable of explaining its low diffusion amid the coffee farmers from the cooperatives, what delays the achievement of the network society. For that, a methodological theoretical reference was built, adequate to the complexity of the research object, and then, one qualitative approach from the concept of the comparative study of case, the connection of the neo-shumpterian approach and the theory of the organizations. It was verified that the limited levei of TI adoption and the process of diffusion are linked to complex factors and independent among themselves, due to the difficulty of the transition to the information society because of cultural questions (the TI used as a control instrument), organizational (the adoption of TI oriented by the fordist paradigm and the non-diffusion as a mechanism of the increase in dependence and power) and institutional (the absence of governmental programs to spread it through the rural society). However, the possibility of change in this scenario was observed, if the implantation of projects as Portal (Cooxupé) and distribution of a management software (Cooparaíso) goes on, to insert more participants in the information society. The participation of the government in this process is fundamental, especial ly in designing politics with educational basis to prepare lhe adoption and use of TI inside the 'new social morphology' - idealized by Castells. Conscious that research does not end 'per si', lhe work has as a niain contribution one new parameter of research to continue the understanding oi social complexity. in which the technology of information is diffused.